The Root Causes Analysis of Indonesia's Fishery Products Rejection in the United States of America and European Countries during 2010 – 2020 - Nurkhasanah, Anissa Aprilia; Suadi, Suadi; Puspita, Indun Dewi (Department of Agro-industrial Technology, University of Brawijaya, 2022)
AbstractThis study aimed to determine the number of cases, causes, and main rejection factors of Indonesia's fishery products by the USA and European markets. Data were obtained from the websites of USFDA (USA) and RASFF (Europe) from 2010 to 2020. Pareto analysis and fishbone diagram were used for analyzing data that informants validated from selected exporters and experts. Within the observed period, there were 2,318 cases of rejection in the USA and 79 in Europe. The highest case was in 2011 in the USA and 2012 in European markets. Based on Pareto analysis of rejection cases, the main factors that accounted for more than 80% of rejections in the USA were filthy and Salmonella; meanwhile, in Europe, were mercury, poor temperature control, Salmonella, histamine, and cadmium. The fishbone diagram result with validation from fishery product exporter shows that human factor, such as the lack of coordination and communication between business actors, especially at the supplier level when selecting raw materials, was considered the cause of rejection (filthy). Establishing well-managed cooperation among business actors within an integrated fish supply chain management is essential to ensure the quality of fishery products.Keywords: Europe, fishery product, rejection, root causes, United States of America AbstrakPenelitian bertujuan untuk mengetahui jumlah kasus, penyebab dan faktor utama penyebab penolakan produk perikanan Indonesia di Pasar Eropa dan Amerika. Data diperoleh dari website USFDA (Amerika) dan RASFF (Eropa) dalam kurung waktu 2010 – 2020. Analisis data yang digunakan yaitu analisis pareto dan diagram tulang ikan, yang divalidasi oleh informan dari eksportir terpilih dan ahli. Hasil penelitian menunjukkan penolakan produk ekspor perikanan Indonesia di pasar Amerika berjumlah 2.318 kasus dan 79 kasus di Eropa dalam kurun waktu penelitian. Penolakan tertinggi terjadi pada tahun 2011 di pasar Amerika dan pada tahun 2012 di Eropa. Hasil analisis data dengan diagram pareto menunjukkan bahwa produk kotor dan Salmonella menyumbang 80% penolakan produk perikanan di Amerika, sedangkan mercury, pengendalian suhu yang tidak bagus, Salmonella, histamine, dan cadmium di pasar Eropa. Hasil analisis diagram tulang ikan dan validasi dengan eksportir menunjukkan bahwa penyebab penolakan untuk pasar Amerika Serikat (yaitu produk kotor) adalah faktor manusia, seperti kurang koordinasi dan komunikasi antar pelaku usaha, khususnya di tingkat supplier. Kerjasama antar pelaku usaha dalam pengelolaan rantai pasok ikan terintegrasi dapat menjamin kualitas produk perikanan yang sesuai standar yang dipersyaratkan.Kata kunci: akar masalah, Amerika Serikat, Eropa, penolakan, produk perikanan